Kitâbu Tehzîbu’t-tehzîb - 880-01 İbn Hacer el-Askalânî, 1372-1449. (Haydarabad Haydarabad Haydarabad)
12 cilt (1. c. 516 sayfa ; 2. c. 454 sayfa ; 3. c. 488 sayfa ; 4. c. 464 sayfa ; 5. c. 391 sayfa ; 6. c. 463 sayfa ; 7. c. 507 sayfa ; 8. c. 470 sayfa ; 9. c. 546 sayfa ; 10. c. 494 sayfa ; 11. c. 453 sayfa ; 12. c. 504 sayfa)